Application of high-strength modified PMMA composite material in field of bionic denture bases

By adding modified nano-silver-carried zirconium phosphate and surfactant-modified nano-zirconium oxide to the PMMA denture foundation, the impact resistance of existing PMMA base materials is solved by combining high-strength modified PMMA composite materials with methyl methacrylate. and the problem of insufficient antibacterial properties have significantly improved the performance and service life of the bionic denture base.

CN119139141APending Publication Date: 2024-12-17SHANGHAI HULIANG BIOMEDICAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411294388.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing PMMA denture base materials have shortcomings in impact strength, bending strength and antibacterial properties, resulting in prone to fracture and oral diseases.

Method used

A high-strength modified PMMA composite material, including modified nano-silver-carried zirconium phosphate and surfactant modified nano-zirconium oxide, combined with methyl methacrylate, was prepared by ball milling and thermoforming processes.

Benefits of technology

It improves the impact strength, bending strength and antibacterial rate of the bionic denture base, improves the biocompatibility in the oral cavity, extends the service life and reduces the incidence of oral diseases.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005045497270000061
    Figure BDA0005045497270000061
  • Figure BDA0005045497270000071
    Figure BDA0005045497270000071
  • Figure BDA0005045497270000072
    Figure BDA0005045497270000072
Patent Text Reader

Abstract

The invention belongs to the technical field of denture materials, and particularly relates to application of a high-strength modified PMMA composite material in the field of bionic denture bases. The bionic denture base material is prepared from the following components in parts by weight: 70 to 90 parts of modified PMMA (Polymethyl Methacrylate) composite material, 5 to 15 parts of zirconium-containing compound and 80 to 110 parts of denture water. During application, the preparation method comprises the following steps: weighing the materials according to the ratio, mixing and ball-milling the modified PMMA composite material and the zirconium-containing compound under a solvent-free condition to obtain mixed powder, then adding the mixed powder and denture water into a reaction kettle, stirring to form a cluster, transferring the materials in the reaction kettle into a denture mold, and carrying out extrusion molding on the denture mold. The base mold is placed in a water bath kettle at the temperature of 80-90 DEG C and heated for 50-60 min, then the water bath kettle is heated to 95-110 DEG C, constant-temperature heating is conducted for 40-60 min, the base is completely cured, heating is finished, the mold is removed after natural cooling, and the bionic denture base prepared from the high-strength modified PMMA composite material is obtained. According to the invention, the toughness and antibacterial activity of the bionic denture base can be improved, so that the service life of the bionic denture base is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of denture materials, and in particular relates to application of a high-strength modified PMMA composite material in the field of bionic denture bases. Background Art

[0002] In today's society, there are still a considerable number of people who have not established a correct concept of oral health and have a weak awareness of oral protection, which has led to increasingly prominent oral health problems and seriously affected people's quality of life. Especially among the elderly, tooth loss is common, so the clinical demand for dentures is increasing.

[0003] Dentures are generally composed of bases and abutments. The base is an important component that supports and fixes the abutments. It has important functions such as transmitting bite force, stabilizing abutments, and protecting oral tissues. Therefore, the performance of the base is crucial to the service life and user experience of removable dentures.

[0004] Polymethyl methacrylate (PMMA) is the most commonly used denture base material in clinical practice. It is widely used in my country for its good color, easy forming, easy repair and low price. However, there are many problems in its use, including lack of mechanical properties such as impact strength and bending strength, and lack of antibacterial effect, which makes this material very easy to break during use, or easily unbalance the oral microecological environment, causing oral diseases such as periodontal disease, caries and denture stomatitis.

[0005] In view of the problems existing in the prior art, how to provide a high-strength modified PMMA composite material for use in the field of bionic denture bases so that the prepared bionic denture bases have better impact strength, bending strength, bending elastic modulus and antibacterial rate, so as to improve the biocompatibility in the oral cavity and extend the service life of the bionic denture base is a problem to be urgently solved by the present invention. Summary of the invention

[0006] The purpose of the present invention is to provide a high-strength modified PMMA composite material for use in the field of bionic denture bases to solve the problems raised in the above background technology.

[0007] To achieve the above object, the present invention provides an application of a high-strength modified PMMA composite material in the field of bionic denture bases, characterized in that the bionic denture base comprises the following components in parts by weight: 70-90 parts of modified PMMA composite material, 5-15 parts of zirconium-containing composite material, and 80-110 parts of denture water;

[0008] The zirconium-containing composite comprises coupling agent-modified nano-silver-loaded zirconium phosphate and surfactant-modified nano-zirconium oxide;

[0009] The dental tray water is methyl methacrylate.

[0010] As a further improvement, the weight ratio of the coupling agent modified nano silver-loaded zirconium phosphate to the surfactant modified nano zirconium oxide is 0.2-1.2.

[0011] In order to have better antibacterial properties, preferably, the coupling agent is a borate coupling agent.

[0012] As a further improvement, the borate coupling agent is at least one of LD-100P, ZB-99 and PRA-20.

[0013] In order to have better impact strength, preferably, the surfactant is a nonionic surfactant.

[0014] As a further improvement, the nonionic surfactant is at least one of polyethylene glycol, polysorbate-65, and lauroyl diethanolamine.

[0015] As a further improvement, the preparation method of the coupling agent modified nano silver-loaded zirconium phosphate is as follows:

[0016] The nanometer silver-loaded zirconium phosphate powder is put into a preheated reactor, and then the mixed solution of the borate coupling agent and the organic solvent ultrasonically mixed is added dropwise while stirring. After the reaction is completed, post-treatment is performed to obtain the modified nanometer silver-loaded zirconium phosphate.

[0017] As a further improvement, the preparation method of the surfactant-modified nano-zirconia is as follows:

[0018] Add nano zirconium oxide and non-ionic surfactant into a flask, place it in an oil bath, reflux and stir, and after the reaction is completed, post-process and obtain modified nano zirconium oxide.

[0019] As a further improvement, the method for preparing the modified PMMA composite material comprises the following steps:

[0020] (1) placing the modified nano-silica and methyl methacrylate monomer in a reactor and stirring to uniformly mix;

[0021] (2) adding a composite initiator to step (1) and polymerizing under an inert gas atmosphere to obtain a composite resin intermediate;

[0022] (3) placing the composite resin intermediate obtained in step (2) under an ultraviolet light source for irradiation reaction to obtain a modified PMMA composite material.

[0023] As a further improvement, the composite initiator comprises initiator 1 and initiator 2;

[0024] The first initiator is an acyl peroxide initiator, and the second initiator is a cationic photoinitiator.

[0025] The application of a high-strength modified PMMA composite material provided by the present invention in the field of bionic denture base comprises the following steps:

[0026] (1) weighing materials according to the above ratio, mixing and ball-milling the modified PMMA composite material and the zirconium-containing composite under solvent-free conditions to obtain a mixed powder;

[0027] (2) Add the mixed powder and the dental base water into a reaction kettle, stir until agglomerates are formed, and then transfer the materials in the reaction kettle into a base mold;

[0028] (3) Place the base mold in a water bath at 90-95° C. and heat for 60-80 min. Then raise the temperature of the water bath to 100-110° C. and heat at a constant temperature for 40-50 min. After heating is terminated, the mold is removed after natural cooling to obtain a solidified bionic denture base.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] The present invention provides an application of a high-strength modified PMMA composite material in the field of bionic denture bases, so that the prepared bionic denture bases have better impact strength, bending strength, bending elastic modulus and antibacterial rate, improve the biocompatibility in the oral cavity, reduce the incidence of oral diseases, and extend the service life of the bionic denture bases. DETAILED DESCRIPTION

[0031] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.

[0032] In the following examples, except for modified nano silver-loaded zirconium phosphate, modified nano zirconium oxide, modified nano silicon dioxide, and cationic photoinitiator, the remaining compound monomers and related reagents used can be purchased from the market. Among them, nano silver-loaded zirconium phosphate was purchased from Changzhou Konada New Materials Technology Co., Ltd., model KND-YA30, nano zirconium oxide (particle size of 50nm) was purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd., model ZT-R50, nano silicon dioxide (particle size of 20nm) was purchased from Nanjing Tianxing New Materials Co., Ltd., model TSP-H10, PMMA material was purchased from Dongguan Chenghao Plastic Raw Materials Co., Ltd., model IRK304-001, and polyethylene glycol solution was purchased from Shanghai McLean Biochemical Technology Co., Ltd., model P815604.

[0033] The preparation method of modified nano silver-loaded zirconium phosphate A comprises the following steps:

[0034] 50 g of silver-loaded zirconium phosphate powder was put into a reactor preheated to 90°C, and then 1.3 g of borate coupling agent ZB-99 and 50 mL of ethanol were added dropwise with stirring after ultrasonic oscillation for 30 min. The speed was 500 rpm and the mixture was stirred continuously for 20 min. The mixture was centrifuged, washed and vacuum dried to obtain modified nano silver-loaded zirconium phosphate A.

[0035] The preparation method of modified nano silver-loaded zirconium phosphate B comprises the following steps:

[0036] 50g of silver-loaded zirconium phosphate powder was put into a reactor preheated to 90°C, and then 2g of silane coupling agent KH-550 and 60mL of ethanol were added dropwise with stirring after ultrasonic oscillation for 30min. The speed was 500rpm and the mixture was stirred continuously for 20min. The mixture was centrifuged, washed and vacuum dried to obtain modified nano silver-loaded zirconium phosphate B.

[0037] The preparation method of modified nano zirconium oxide A comprises the following steps:

[0038] 20 g of nano zirconium oxide and 150 mL of polyethylene glycol solution were added into a 500 mL flask, placed in an oil bath, refluxed and stirred at 150° C. for 60 min at a stirring speed of 300 rpm, the reaction was stopped, filtered, washed, and vacuum dried to obtain modified nano zirconium oxide A.

[0039] The preparation method of modified nano zirconium oxide B comprises the following steps:

[0040] 10 g of nano zirconium oxide, 3 g of sodium dodecylbenzene sulfonate and 100 mL of deionized water were added into a 250 mL flask, placed in an oil bath, refluxed and stirred at 90° C. for 60 min at a stirring speed of 300 rpm, the reaction was stopped, filtered, washed, and vacuum dried to obtain modified nano zirconium oxide B.

[0041] The preparation method of modified nano silicon dioxide comprises the following steps:

[0042] Accurately weigh 5 g of nano-silica powder and add it to a 500 mL round-bottom flask, then add 200 mL of anhydrous ethanol, ultrasonically disperse for 30 min, drop 1.0 g of KH-570 coupling agent, and then heat to 80 ° C., reflux for 2 h, centrifuge, wash, and vacuum dry to obtain modified nano-silica.

[0043] The preparation steps of cationic photoinitiator are as follows:

[0044] In a 100 mL long-necked flask, 2.2 mmol 2-mercaptobenzoxazole and 1 mmol 1,4-diiodobenzene were added in sequence, dissolved with 4 mL N,N-dimethylamide, and then 0.1 mmol cuprous iodide and 15 mmol potassium hydroxide were added. The flask was placed in a microwave reactor, the power was set to 30 W, and the reaction was carried out for 20 min. After the flask was cooled to room temperature, the reaction mixture was transferred to a separatory funnel, extracted with ethyl acetate, and the solvent in the organic phase was dried to obtain a crude product. The crude product was separated by column chromatography with V (petroleum ether): V (ethyl acetate) = 1:20 to obtain intermediate 1;

[0045] Next, 1 mmol of intermediate 1 and 2.4 mmol of diphenyliodonium trifluoromethanesulfonate were added in sequence to a 50 mL round-bottom flask equipped with a stirrer, dissolved with 2 mL of 1,1,2,2-tetrachloroethane, and then 0.1 mmol of cuprous iodide and 0.1 mmol of copper powder were added. The temperature was raised to 110°C and the reaction was carried out for 2 h. After the reaction liquid was cooled to room temperature, the solvent was removed by rotation and separated by column chromatography to obtain a cationic photoinitiator.

[0046] The preparation method of the modified PMMA composite material comprises the following steps:

[0047] 5 g of modified nano-silica and 95 g of methyl methacrylate monomer were stirred until they were uniformly mixed at a stirring speed of 500 rpm. Then, 1.1 g of benzoyl peroxide and 0.4 g of a cationic photoinitiator were added as a composite initiator, and polymerization was carried out under a nitrogen atmosphere at a stirring speed of 700 rpm, a temperature of 90° C., and a stirring time of 30 min to obtain a composite resin intermediate. Finally, the composite resin intermediate was placed under an ultraviolet light source for irradiation reaction to obtain a PMMA composite material modified with a nano-silica inorganic filler, wherein the light source band was 280-295 nm and the irradiation reaction was 20 min.

[0048] The preparation method of the bionic denture base of Examples 1-4 and Comparative Examples 2-3 comprises the following steps:

[0049] (1) adding the modified PMMA composite material and the zirconium-containing composite into a mixing ball mill without solvent, grinding at 300 rpm for 15 min to obtain a mixed powder;

[0050] (2) Add the mixed powder and dental tray water into a reactor and stir at 200 rpm for 30 min. After agglomeration, transfer the materials in the reactor to a base mold;

[0051] (3) Place the base mold in a water bath at 90°C and heat for 60 minutes. Then raise the temperature of the water bath to 110°C and heat at a constant temperature for 40 minutes. After heating is terminated, the mold is removed after natural cooling to obtain a solidified bionic denture base.

[0052] The preparation method of the bionic denture base of Comparative Example 1 comprises the following steps:

[0053] (1) adding PMMA material and zirconium-containing composite into a mixing ball mill without solvent, grinding at 300 rpm for 15 min to obtain mixed powder;

[0054] (2) Add the mixed powder and dental tray water into a reactor and stir at 200 rpm for 30 min. After agglomeration, transfer the materials in the reactor to a base mold;

[0055] (3) Place the base mold in a water bath at 90° C. and heat for 60 min. Then raise the temperature of the water bath to 110° C. and heat at a constant temperature for 40 min. After heating is terminated, the mold is removed after natural cooling to obtain a solidified bionic denture base.

[0056] The components and contents used in Examples 1-4 and Comparative Examples 1-3 are shown in Table 1 below:

[0057] Table 1

[0058]

[0059]

[0060] The impact strength, bending strength, bending elastic modulus and antibacterial rate of the bionic denture base prepared from the high-strength modified PMMA composite material obtained in Examples 1-4 and Comparative Examples 1-3 were tested, and the test method was as follows:

[0061] Impact strength: measured according to ASTM D256-1997;

[0062] Bending strength: measured according to GB / T9341-2008 "Determination of bending properties of plastics";

[0063] Bending elastic modulus: measured according to GB / T9341-2008 "Determination of bending properties of plastics";

[0064] Antibacterial rate: Determined by the film adhesion method in QB / T2591-2003 "Test methods and antibacterial effects of antibacterial plastics".

[0065] The test results are shown in Table 2:

[0066] Table 2

[0067]

[0068] It can be seen from the test results of Example 2 and Comparative Example 1 in Table 2 that, compared with the unmodified PMMA material, the bionic denture base prepared using the high-strength modified PMMA composite material obtained by using the modified PMMA composite material has better bending strength and bending elastic modulus.

[0069] It can be seen from the test results of Example 2 and Comparative Example 2 that the antibacterial rate of the bionic denture base prepared by the high-strength modified PMMA composite material prepared by using the borate coupling agent modified nano-silver-loaded zirconium phosphate has a better effect than that of the nano-silver-loaded zirconium phosphate modified by silane coupling agents such as KH-550.

[0070] It can be seen from the test results of Example 2 and Comparative Example 3 that the bionic denture base prepared with the high-strength modified PMMA composite material prepared by using nano-zirconium oxide modified by non-ionic surfactants has better impact strength than that prepared by nano-zirconium oxide modified by anionic surfactants such as sodium dodecylbenzenesulfonate.

[0071] It can be seen from the test results of Examples 1-3 and Example 4 that when the addition ratio of the coupling agent-modified nano-silver-loaded zirconium phosphate and the surfactant-modified nano-zirconium oxide is within an appropriate range, the bionic denture base prepared from the high-strength modified PMMA composite material has better impact strength, flexural strength, flexural elastic modulus and antibacterial rate.

[0072] It can be seen from the test results of Examples 1-3 that the bionic denture base prepared from a high-strength modified PMMA composite material prepared by the preparation method provided by the present invention has better impact strength, bending strength, bending elastic modulus and antibacterial rate, indicating that it has good toughness, is not prone to breakage, and has good antibacterial properties, which can reduce the incidence of oral diseases.

[0073] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. Application of a high-strength modified PMMA composite material in the field of bionic denture base, It is characterized in that The bionic denture base comprises the following components in parts by weight: 70-90 parts of modified PMMA composite material, 5-15 parts of zirconium-containing composite material, and 80-110 parts of denture water; The zirconium-containing composite comprises coupling agent-modified nano-silver-loaded zirconium phosphate and surfactant-modified nano-zirconium oxide; The dental tray water is methyl methacrylate.

2. Application of a high-strength modified PMMA composite material according to claim 1 in the field of bionic denture bases, It is characterized in that The weight ratio of the coupling agent modified nano silver-loaded zirconium phosphate to the surfactant modified nano zirconium oxide is 0.2-1.

2.

3. Application of a high-strength modified PMMA composite material according to claim 1 or 2 in the field of bionic denture bases, It is characterized in that The coupling agent is a borate coupling agent.

4. Application of a high-strength modified PMMA composite material according to claim 3 in the field of bionic denture bases, It is characterized in that The borate coupling agent is at least one of LD-100P, ZB-99 and PRA-20.

5. Application of a high-strength modified PMMA composite material according to claim 1 or 2 in the field of bionic denture bases, It is characterized in that The surfactant is a nonionic surfactant.

6. Application of the high-strength modified PMMA composite material according to claim 5 in the field of bionic denture bases, It is characterized in that The nonionic surfactant is at least one of polyethylene glycol, polysorbate-65 and lauroyl diethanolamine.

7. Application of the high-strength modified PMMA composite material according to claim 1 in the field of bionic denture bases, It is characterized in that The preparation method of the coupling agent modified nano silver-loaded zirconium phosphate is as follows: The nanometer silver-loaded zirconium phosphate powder is put into a preheated reactor, and then the mixed solution of the borate coupling agent and the organic solvent ultrasonically mixed is added dropwise while stirring. After the reaction is completed, post-treatment is performed to obtain the modified nanometer silver-loaded zirconium phosphate.

8. Application of the high-strength modified PMMA composite material according to claim 1 in the field of bionic denture bases, It is characterized in that The preparation method of the surfactant-modified nano zirconium oxide is as follows: Add nano zirconium oxide and non-ionic surfactant into a flask, place it in an oil bath, reflux and stir, and after the reaction is completed, post-process and obtain modified nano zirconium oxide.

9. Application of the high-strength modified PMMA composite material according to claim 1 in the field of bionic denture bases, It is characterized in that The preparation method of the modified PMMA composite material comprises the following steps: (1) placing the modified nano-silica and methyl methacrylate monomer in a reactor and stirring to uniformly mix; (2) adding a composite initiator to step (1) and polymerizing under an inert gas atmosphere to obtain a composite resin intermediate; (3) placing the composite resin intermediate obtained in step (2) under an ultraviolet light source for irradiation reaction to obtain a modified PMMA composite material.

10. Application of the high-strength modified PMMA composite material according to claim 1 in the field of bionic denture bases, It is characterized in that When applied, the following steps are included: (1) weighing materials according to the above ratio, mixing and ball-milling the modified PMMA composite material and the zirconium-containing composite under solvent-free conditions to obtain a mixed powder; (2) Add the mixed powder and the dental base water into a reaction kettle, stir until agglomerates are formed, and then transfer the materials in the reaction kettle into a base mold; (3) Place the base mold in a water bath at 90-95° C. and heat for 60-80 min. Then raise the temperature of the water bath to 100-110° C. and heat at a constant temperature for 40-50 min. After heating is terminated, the mold is removed after natural cooling to obtain a solidified bionic denture base.